Experiences of women who reported sexual assault at a provincial hospital, South Africa - Jeanette M. Sebaeng; Mashudu Davhana- Maselesele; Eva Manyedi (AOSIS, 2016)
Background: Sexual assault poses a serious health problem to both the survivor and the health system. Experiencing sexual assault requires women to seek medical and psychological assistance as part of their journey towards recovery. This study examined the experiences of women who received post-sexual assault services from a specialised care centre within a provincial hospital. Methods: A qualitative, exploratory and contextual design was used to explore and describe experiences of women. Data were obtained through individual in-depth interviews from a total of 18 women aged between 18 and 55 years. Interviews were supplemented by the researcher's field notes and audiotape recordings. Results: Findings yielded two main themes: Women expressed their lived experiences of sexual assault characterised by different forms of trauma. The second theme was an expression of a need for safety and support. Conclusion: Women who experience sexual assault are left with devastating effects such as physical and psychological harm and social victimisation. There is also a need for safety and support towards the recovery of these women. This study recommends that professional practitioners involved in the management of sexual assault be sensitised regarding the ordeal experienced by women and stop perceiving survivors as crime scene 'clients' from whom only medico-legal evidence has to be collected. Professional practitioners and family members must be supportive, non-judgemental and considerate of the dignity of survivors. The establishment of sexual assault response teams (SART) is also recommended. There should also be inter-professional education for better coordination of services rendered to sexually assaulted women.